Identification of a Cellular Protein That Interacts and Synergizes with the RTA (ORF50) Protein of Kaposi's Sarcoma-Associated Herpesvirus in Transcriptional Activation - Wang, Shizhen (American Society for Microbiology, 2001)
Lytic reactivation of Kaposi's sarcoma-associated herpesvirus (KSHV), or human herpesvirus 8, from latency requires transcriptional transactivation by the viral protein RTA encoded by the ORF50 gene. Very little is known about how RTA functions and the cellular factors that may be involved in its transactivation function. Using the yeast two-hybrid system, we have identified a human cellular protein that can interact with KSHV RTA. The cellular protein, referred to as the human hypothetical protein MGC2663 by GenBank, is encoded by human chromosome 19. This protein is 554 amino acids (aa) in size and displays sequence similarity with members of the Krueppel-associated box–zinc finger proteins (KRAB-ZFPs). MGC2663 expression could be detected in all primate cell lines tested, and its expression level was neither stimulated nor inhibited by RTA. MGC2663 specifically synergizes with RTA to activate viral transcription, and overexpression of MGC2663 in the presence of RTA further enhances RTA transactivation of several viral promoters that were identified as targets for RTA. Coimmunoprecipitation and pull-down assays further demonstrated that MGC2663 interacts with RTA both in vivo and in vitro, and the N-terminal 273 aa of KSHV RTA and the potential zinc finger domain of MGC2663 are required for their interaction. Our results indicate that this novel human cellular protein, MGC2663, named K-RBP (KSHV RTA binding protein) due to its RTA binding feature, specifically interacts with the KSHV RTA protein and functions as a cellular RTA cofactor to activate viral gene expression. Though its normal cellular function needs to be further studied, K-RBP may play a significant role in mediating RTA transactivation in vivo.